Structural Optimization of Compact Spherical Wind-Solar Hybrid Power System - Wei, Huili; Pan, Tianhong; Zhu, Mingxing; Tao, Jun (Journal of electrical engineering & technology, 2021)
Conventional wind-solar hybrid power systems (WS-HPSs) have certain structural drawbacks owing to their large size and the difficulty in adjusting the tilt angle of the solar panels. To address these limitations, this study proposes a compact spherical wind-solar hybrid power system (CSWS-HPS). Furthermore, to investigate the aerodynamic performance of the designed CSWS-HPS, a computational fluid dynamics model of the wind rotor was established using the Reynolds-averaged Navier–Stokes equations, renormalization group k-ε turbulence model, and sliding mesh. Subsequently, the flow field distribution of velocity and pressure under different numbers of blades, blade installation angles, and tip-speed ratios (TSRs) were analyzed by performing a three-dimensional simulation of the CSWS-HPS. The monitored values of the moment coefficients were used to calculate the power coefficient value of the wind turbine to obtain the optimum structural parameters, which in turn provided the optimal values for the CSWS-HPS model. The simulation results revealed that the CSWS-HPS achieved considerable power generation efficiency in comparison with that of conventional hybrid systems. In addition, the CSWS-HPS is more compact in size and does not emit CO 2 .